2013
DOI: 10.1177/030089161309900201
|View full text |Cite
|
Sign up to set email alerts
|

Association of Breast Cancer Subtypes and Body Mass Index

Abstract: The risk of specific breast cancer subtypes may not be associated with BMI in pre- and postmenopausal breast cancer. However, obesity might be related to an increased risk of premenopausal hormone receptor-negative breast cancer. Further studies are needed for clarification of the probable mechanisms in the pathogenesis of premenopausal hormone receptor-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…However, these associations were not statistically significant [30]. Some other studies suggested that the association between BMI and an increased risk of breast cancer might be limited to pre-menopausal hormone receptor-negative breast cancer [3132]. This suggests that the association between BMI and cancer varies by cancer subtype, which warrants future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, these associations were not statistically significant [30]. Some other studies suggested that the association between BMI and an increased risk of breast cancer might be limited to pre-menopausal hormone receptor-negative breast cancer [3132]. This suggests that the association between BMI and cancer varies by cancer subtype, which warrants future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, joint detection of tumor markers is of great importance in the early discovery and treatment of patients as well as the judgment on progression and prognosis of disease. The previous studies revealed that the prognosis of patients with breast cancer who had both negative estrogen receptor (ER) and progesterone receptor (PR) was very poor, suggesting that detection of ER and PR expression plays a key role in judging the prognosis of disease (Patel et al, 2013;Petekkaya et al, 2013). Vascular endothelial growth factor (VEGF) capable of promoting angiogenesis exerts an important effect in the process of genesis, development, metastasis and recurrence of various tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The Public around the world paying attention to the prevalence of Obesity 1 due to its association with chronic diseases like breast cancer 2 , COPD 3 and soon. In human beings serum Uric acid is end product of purine metabolism 4 .…”
Section: Introductionmentioning
confidence: 99%